2020
DOI: 10.3390/ijms21031118
|View full text |Cite
|
Sign up to set email alerts
|

Network between Cytokines, Cortisol and Occupational Stress in Gas and Oilfield Workers

Abstract: To test whether gas and oil field work is accompanied by stress and altered immune function, the perception of workplace stress, levels of salivary cortisol, plasma levels, and mononuclear cell production of cytokines were examined in 80 healthy workers recruited among a population of operators on gas and oilfields. Specific questionnaires for determining the perception of anxiety, occupational stress, and subjective symptoms were administered. Salivary cortisol and cytokines plasma levels were evaluated by El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…In 2013, Wen-Qing Li et al found an association between inflammatory skin disease (psoriasis) and night shift postulating that the increased risk could be related to a diminished ability of the pineal gland to produce melatonin (19). Furthermore, we have to consider the possible role of occupational stress, related to the work strain of HCWs, in the development of skin disorders according to data from literature (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, Wen-Qing Li et al found an association between inflammatory skin disease (psoriasis) and night shift postulating that the increased risk could be related to a diminished ability of the pineal gland to produce melatonin (19). Furthermore, we have to consider the possible role of occupational stress, related to the work strain of HCWs, in the development of skin disorders according to data from literature (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Future work hopes to collect for a longer study period using a larger population pool which would potentially increase the statistical validity of the study and improve the foundation of knowledge. Ideally, a greater depth and breadth of knowledge will lead towards the prevention of illnesses associated with chronic stress so as to reduce workplace absenteeism or economic repercussions [53]. Further, we hope to collect data on alpha-amylase fluctuations in addition to changes in salivary cortisol levels.…”
Section: Limitationsmentioning
confidence: 99%
“…As such, detecting and mitigating stress experienced by the individual with dementia in a quick and timely manner can reduce the occurrence and potential intensity of the dementia-related difficulties. Furthermore, there is a link between work stress and dementia, with long-term exposure to occupational stress being linked to an increased risk of developing dementia [26][27][28]. Thus, the timely detection and mitigation of work stress could potentially reduce the risk of an individual developing dementia in later life, further linking the domains of dementia and stress research.…”
Section: Pivot and Justificationmentioning
confidence: 99%